Impact of Inflammation on Voriconazole Exposure in Critically ill Patients Affected by Probable COVID-19-Associated Pulmonary Aspergillosis - Milo Gatti; Giacomo Fornaro; Zeno Pasquini; Andrea Zanoni; Michele Bartoletti; Pierluigi Viale; Federico Pea (MDPI AG, 2023)
(1) Background: To explore the impact of the degree of inflammation on voriconazole exposure in critically ill patients affected by COVID-associated pulmonary aspergillosis (CAPA); (2) Methods: Critically ill patients receiving TDM-guided voriconazole for the management of proven or probable CAPA between January 2021 and December 2022 were included. The concentration/dose ratio (C/D) was used as a surrogate marker of voriconazole total clearance. A receiving operating characteristic (ROC) curve analysis was performed by using C-reactive protein (CRP) or procalcitonin (PCT) values as the test variable and voriconazole C/D ratio > 0.375 (equivalent to a trough concentration [Cmin] value of 3 mg/L normalized to the maintenance dose of 8 mg/kg/day) as the state variable. Area under the curve (AUC) and 95% confidence interval (CI) were calculated; (3) Results: Overall, 50 patients were included. The median average voriconazole Cmin was 2.47 (1.75-3.33) mg/L. The median (IQR) voriconazole concentration/dose ratio (C/D) was 0.29 (0.14-0.46). A CRP value > 11.46 mg/dL was associated with the achievement of voriconazole Cmin > 3 mg/L, with an AUC of 0.667 (95% CI 0.593-0.735; p < 0.001). A PCT value > 0.3 ng/mL was associated with the attainment of voriconazole Cmin > 3 mg/L (AUC 0.651; 95% CI 0.572-0.725; p = 0.0015). (4) Conclusions: Our findings suggest that in critically ill patients with CAPA, CRP and PCT values above the identified thresholds may cause the downregulation of voriconazole metabolism and favor voriconazole overexposure, leading to potentially toxic concentrations.